Community outreach programmeme as an integral part of clinical legal education: a socio-legal study - S. Ghanghash (Law and Safety)
This study explores the integration of community outreach programmes in clinical legal education from a socio-legal perspective. Using Doctrinal research methods, the study examines the impact of community outreach programmes on students’ legal education, and the benefits to the communities served. Results indicate that the programmes enhance students’ legal skills, promote social justice, and foster community engagement. Additionally, the programmes provide communities with much-needed legal services and promote access to justice. The study concludes that community outreach programmes should be an integral part of clinical legal education to promote socially responsible legal education and advance social justice.